Exploring Sustainable Tourism Through the Theory of Planned Behavior: A Study in Pemuteran Tourism Village, Buleleng, Bali - Sekar, Maria Tabitha; I Gusti Putu Bagus Sasrawan Mananda; Ni Putu Ratna Sari (International Journal of Economics, Business and Innovation Research, 2025)
Unsustainable tourism can cause environmental damage, cultural degradation, and socio-economic inequality. Pemuteran Tourism Village in Bali applies sustainable tourism principles to balance economic benefits, environmental preservation, and community empowerment. This study aims to analyze tourist behavior in supporting sustainable tourism in the destination using Theory of Planned Behavior (TPB) as the theoretical framework. A quantitative approach was used with a sampling of 100 respondents, namely foreign tourists who have visited Pemuteran Tourism Village and have an interest in sustainable tourism. The sampling technique applied was purposive sampling, with data collection through questionnaires. Data were analyzed using the Partial Least Square-Structural Equation Modeling (PLS-SEM) method with SmartPLS software, supported by qualitative descriptive analysis. The results showed that tourists' intention to participate in sustainable tourism, as predicted by the TPB model, comprising attitudes, subjective norms, and perceived behavioral control significantly influences their actual behavior in practicing sustainable tourism at the destination.